2000
DOI: 10.1046/j.1526-0968.2000.004002155.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocytapheresis as a Possible Cancer Treatment

Abstract: Guest Editor's Introduction: The granulocyte removal column was developed by Japan Immunoresearch Laboratories Co. based upon the hypothesis that the normalization of granulocyte‐to‐lymphocyte ratio would be beneficial for the treatment of cancer since the ratio is increased due to the cancer leukocytosis. The column consists of cellulose acetate beads with a diameter of 2 mm, which removes granulocytes and monocytes from blood with no significant changes in the number of lymphocytes or platelets. The clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 5 publications
1
18
0
Order By: Relevance
“…The number of granulocytes showed an upward trend over time after implantation in both the 1x10 6 (P<0.0001) and 1x10 5 (P=0.035) cell groups. In the 1x10 6 cell groups, the number of granulocytes measured on days 11, 14 and 17 after implantation (groups F-H) was significantly increased in comparison with the control group (normal mice, 0.309±0.089), while the number of lymphocytes peaked on day 11 after implantation, then decreased. In the 1x10 5 cell groups, the number of granulocytes on days 11, 14 and 17 after implantation (groups A-C) showed no significant increase in comparison with the control group.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The number of granulocytes showed an upward trend over time after implantation in both the 1x10 6 (P<0.0001) and 1x10 5 (P=0.035) cell groups. In the 1x10 6 cell groups, the number of granulocytes measured on days 11, 14 and 17 after implantation (groups F-H) was significantly increased in comparison with the control group (normal mice, 0.309±0.089), while the number of lymphocytes peaked on day 11 after implantation, then decreased. In the 1x10 5 cell groups, the number of granulocytes on days 11, 14 and 17 after implantation (groups A-C) showed no significant increase in comparison with the control group.…”
Section: Resultsmentioning
confidence: 90%
“…Several investigators have suggested that the G/L ratio is a good indicator for the evaluation of the condition of a tumour-bearing host (4,6), although the correlation between granulocytes and lymphocytes or between the G/L ratio and clinicopathologic factors is unclear (8).…”
Section: Discussionmentioning
confidence: 99%
“…It was thought that lymphocytes were depleted by activated myeloid leucocytes. The Adacolumn was developed to take away the excess and activated myeloid cells, hoping that this might lead to enhanced lymphocyte function [26,76,77]. Figure 8 summarizes the actions which ideally should be expected from therapeutic GMA in patients with IBD and other immune-related complications.…”
Section: Advanced Cancermentioning
confidence: 99%
“…In addition to the above, Tabuchi et al (46,47) reported that when neutrophils were removed from circulating blood of rabbits with tumors or patients with recurrent metastatic tumors by apheresis, the cancers were extensively undersized, suggesting that neutrophils are relevant to the development of cancer. Currently, neutrophils are recognized as the cells to modify tumor growth, angiogenesis, and metastasis (48).…”
Section: Discussionmentioning
confidence: 99%